2014
DOI: 10.1371/journal.pone.0105184
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Checking Different Sources of Mobility Information

Abstract: The pervasive use of new mobile devices has allowed a better characterization in space and time of human concentrations and mobility in general. Besides its theoretical interest, describing mobility is of great importance for a number of practical applications ranging from the forecast of disease spreading to the design of new spaces in urban environments. While classical data sources, such as surveys or census, have a limited level of geographical resolution (e.g., districts, municipalities, counties are typi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
106
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 44 publications
(60 reference statements)
5
106
0
7
Order By: Relevance
“…The reliability of Twitter data in mobility studies has been validated in the work of Lenormand et al (2014), who compared the data from Twitter, mobile telephony and official data (censuses), and concluded that the three information sources offer comparable results. However, no research has been found in which these new data sources (mobile telephony, social networks and others) have been used as a proxy for the variability in destinations' attractiveness in the study of dynamic accessibility.…”
Section: Introductionmentioning
confidence: 98%
“…The reliability of Twitter data in mobility studies has been validated in the work of Lenormand et al (2014), who compared the data from Twitter, mobile telephony and official data (censuses), and concluded that the three information sources offer comparable results. However, no research has been found in which these new data sources (mobile telephony, social networks and others) have been used as a proxy for the variability in destinations' attractiveness in the study of dynamic accessibility.…”
Section: Introductionmentioning
confidence: 98%
“…Data provided by communication tools are opening up new opportunities for studying sociospatial behaviors (33)(34)(35)(36). MP call detail records were used in the past for studying human mobility patterns at the individual level (37)(38)(39) or for mapping human movements and activities using aggregated data (40)(41)(42)(43)(44). Most of these studies focused on specific cities or city neighborhoods or groups, and were aimed at understanding traffic flows (40), mapping the intensity of human activities at different times (42)(43)(44), or exploring seasonality in foreign tourist numbers and destinations (45,46).…”
mentioning
confidence: 99%
“…MP call detail records were used in the past for studying human mobility patterns at the individual level (37)(38)(39) or for mapping human movements and activities using aggregated data (40)(41)(42)(43)(44). Most of these studies focused on specific cities or city neighborhoods or groups, and were aimed at understanding traffic flows (40), mapping the intensity of human activities at different times (42)(43)(44), or exploring seasonality in foreign tourist numbers and destinations (45,46). Population movement analyses based on MP data are particularly promising for improving responses to disasters (47,48) and for planning malaria elimination strategies (49)(50)(51).…”
mentioning
confidence: 99%
“…Phone based positioning does not depend on a specific application platform, such as Twitter or Foursquare/Swarm. However, obtaining a cohesive set of spatio-temporal locations from phone records across multiple countries appears to be challenging, given that most studies that analyze mobility from phone records are geographically limited to the city level [60,61] or country level [62], with only a few exceptions that extend beyond national or continental boundaries [63].…”
Section: Summary and Discussionmentioning
confidence: 99%